Stereotype threat spillover how coping with threats to social identity affects aggression, eating, decision making. and attention. [article]. - Inzlicht, Micheal
Stereotype threat spillover a situational predicament in which coping with the stress of stereotype confirmation leaves one in a depleted volitional state and thus less likely to engage in effortful self-control in a variety of domains. We examined this phenomenon in 4 studies in which we had participants cope with stereotype and social identity threat and then measured their performance in domains in which stereotypes were not "in the air." In study 1 we examined whether taking a threatening math test could lead women to respond aggressively. In study 2 we investigated whether coping with a threatening math test could lead women to indulge themselves into a unhealthy food later on and examined the moderation of these effect by personal characteristics that contribute to identity-threat appraisals. In study 3 we investigated whether vividly remembering an experience of social identity-threat results in risky decision making. Finally, in Study 4 we asked whether coping with threat could directly influence attentional control and whether the effect was implemented by inefficient performance monitoring, as assessed by electroencephalography. Our results indicate that stereotype threat can spill over and impact self-control in a diverse array of nonstereotyped domains. These results reveal the potency of stereotype threat and that its negative consequences might extend further than was previously thought. -- (from the author)
Keywords: Stereotype threat; Self-control.; Stress and coping; Neuroscience; Ego depletion